2010
DOI: 10.1007/s12262-010-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinically monitored delay-A valid option in cases with doubtful diagnosis of acute appendicitis

Abstract: Aim To evaluate the effect of delayed surgery after a period of observation in patients with doubtful diagnosis of acute appendicitis in the form of improvement in negative appendectomy rates and the incidence of complications. Materials and methodsOne hundred twelve patients operated with the diagnosis of acute appendicitis between May 2008 to June 2009 were included in this retrospective study. They were divided into two groups based on timing of surgery after admission. These two groups were studied in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The beginning of in‐hospital delay was defined as arrival or physical examination in the emergency department in 22 studies, as clinical or radiological diagnosis in seven studies, and as hospital admission in 14 studies. In 40 studies complicated appendicitis was a reported outcome measure, 19 studies reported SSI, 19 reported wound infection, 16 reported postoperative intra‐abdominal abscess and 15 studies reported postoperative morbidity as an outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…The beginning of in‐hospital delay was defined as arrival or physical examination in the emergency department in 22 studies, as clinical or radiological diagnosis in seven studies, and as hospital admission in 14 studies. In 40 studies complicated appendicitis was a reported outcome measure, 19 studies reported SSI, 19 reported wound infection, 16 reported postoperative intra‐abdominal abscess and 15 studies reported postoperative morbidity as an outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that surgical appendectomy is the gold standard of AA, there are studies of conservative antibiotic treatment with low morbidity and mortality rate, and a recurrence rate between 7-15 % [ 5 ]. On the other hand, delay of operative treatment can stimulate the development of complications [ 6 - 8 ]. Co-morbidity and negative appendectomy are strongly related with higher mortality, where co-morbidity, diagnostic failure, and the anesthetic or surgical trauma are the important factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies we reviewed indicate that early surgical intervention also can lead to poor patient outcomes 32,29 . Early surgery may increase the risk of removing a healthy appendix (ie, a negative appendectomy), 32,39 which causes the patient to have unnecessary surgery, placing them at risk for complications 40 . The SSAT practice guidelines for treating appendicitis state that a negative appendectomy rate of 15% is acceptable 22 .…”
Section: Discussionmentioning
confidence: 97%